The genome sequence of the white-throated dipper, Cinclus cinclus (Linnaeus, 1758) [version 1; peer review: 2 approved] - Stuart P. Sharp (Wellcome Open Research)
We present a genome assembly from a juvenile male Cinclus cinclus (the white-throated dipper; Chordata; Aves; Passeriformes; Cinclidae). The genome sequence has a total length of 1,170.80 megabases. Most of the assembly (93.88%) is scaffolded into 39 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 18.67 kilobases in length.